Wearable Electronics: Mechanically Durable and Flexible Thermoelectric Films from PEDOT:PSS/PVA/Bi0.5Sb1.5Te3 Nanocomposites (Adv. Electron. Mater. 4/2017). (April 2017) - Zhang, Ting; Li, Kaiwei; Li, Chengchao; Ma, Shaoyang; Hng, Huey Hoon; Wei, Lei
Abstract : The fabrication of mechanically durable and flexible thermoelectric films using a blend of polyvinyl alcohol, PEDOT:PSS, and Bi0.5 Sb1.5 Te3 nanocrystals is reported by T. Zhang et al in article number 1600554. The resulting nanocomposite films exhibit good thermoelectric performance and meet the mechanical requirements necessary for use in both textile manufacturing and flexible and wearable energy‐generating devices.